2017
DOI: 10.1007/s00276-017-1842-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of choanal atresia on development of the paranasal sinuses and turbinates

Abstract: The complete absence of nasal unilateral airflow had no effect on the development of the PNS and the middle and inferior turbinate. Moreover, mucosal thickness in the sinuses was similar to that in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Choanal atresia (CA) is a congenital disorder which results in the complete obstruction of the posterior choanae and therefore blocks airflow between the nose and nasopharynx (Terzi et al, 2017). Unilateral CA is often diagnosed and treated after facial development and therefore serves as a useful model in assessing the role that air flow has in paranasal sinus development (Guimaraes et al, 2007).…”
Section: Pathological Processes That Affect Sinus Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Choanal atresia (CA) is a congenital disorder which results in the complete obstruction of the posterior choanae and therefore blocks airflow between the nose and nasopharynx (Terzi et al, 2017). Unilateral CA is often diagnosed and treated after facial development and therefore serves as a useful model in assessing the role that air flow has in paranasal sinus development (Guimaraes et al, 2007).…”
Section: Pathological Processes That Affect Sinus Developmentmentioning
confidence: 99%
“…Unilateral CA is often diagnosed and treated after facial development and therefore serves as a useful model in assessing the role that air flow has in paranasal sinus development (Guimaraes et al, 2007). Cephalometric and cross sectional imaging of maxillary, sphenoid and frontal sinuses being compared with either control populations or contralateral sinus volume interestingly have not demonstrated decreased sinus volumes (Behar & Todd, 2000; Diner et al, 1986; Terzi et al, 2017). Furthermore, some studies have suggested the atretic side is either symmetrical to or even larger than the non‐atretic side (Guimaraes et al, 2007; Leclerc & Leclerc, 2009).…”
Section: Pathological Processes That Affect Sinus Developmentmentioning
confidence: 99%
“…Односторонняя атрезия хоан не нарушала пневматизацию, не влияла на толщину слизистой оболочки и объем верхнечелюстных, лобных и клиновидных пазух [53,54] или происходило увеличение объема ВЧП на стороне атрезии [53]. Ввиду того что такая патология встречается достаточно редко, в литературе не было обнаружено достоверных данных по поводу влияния атрезии хоан на развитие синусита.…”
Section: цель работыunclassified